LH/hCG-Receptor Expression May Have a Negative Prognostic Value in Low-Risk Endometrial Cancer - Noci, Ivo; Sorbi, Flavia; Mannini, Luca; Projetto, Elisabetta; Pillozzi, Serena; Ghizzoni, Viola; Lottini, Tiziano; Moncini, Daniela; Baroni, Gianna; Mungai, Francesco; Arcangeli, Annarosa; Fambrini, Massimiliano (Frontiers in Oncology, 2016)
Introduction: A 51 years-old woman was diagnosed with endometrial cancer and underwent surgical staging. Pathologic evaluation showed a 2x1 cm G2 endometrioid endometrial cancer with a 30% myometrial deep invasion (FIGO stage 1A). The patient was classified as low-risk of recurrence and no adjuvant treatment was offered. Six months after surgery, the patient developed an early vescico-vaginal recurrence and chemotherapy treatment was started. Few months later a subsequent involvement of vaginal wall, ileum and omentum was detected and the patient underwent second surgery. Background: LH/hCG-receptor (LH/hCG-R) expression has been previously reported to be associated with an invasive phenotype in endometrial cancer cells. Moreover, in a preclinical mouse model of EC behaves as a pro metastatic molecular device. Discussion: We analysed the expression level of LH/hCG-R in cancer specimens collected during surgeries. Molecular and immunohistochemical analysis showed a strong expression of both mRNA and protein for LH/hCG-R in all specimens. Conclusion: LH/hCG-R expression may be assessed together with other clinicopathological parameters in order to better predict the risk of recurrence in low-risk endometrial cancer patients. Further clinical trials are warranted in order to validate LH/hCG-R as biomarker in endometrial cancer.